New protocol for kinetic assay seeding ability recovery “KASAR” from formalin-fixed paraffin-embedded tissues - Hepker, Monica; Clabaugh, Griffin; Jin, Huajun; Kanthasamy, Anumantha G. (Frontiers in Molecular Biosciences, 2023)
The RT-QuIC alpha-synuclein protein kinetic seeding assay has been very useful for detecting pathological aggregates in various synucleinopathies including Parkinson’s disease. This biomarker assay relies on fresh frozen tissue to effectively seed and amplify aSyn aggregating protein. However, the major challenge posed by significantly reduced amplification of formalin-fixed tissues in the assay suggests that formalin fixation deterred monomer interaction with the sample seed and depressed subsequent protein aggregation. To overcome this challenge, we developed a kinetic assay seeding ability recovery (KASAR) protocol to maintain the integrity of the tissue and seeding protein. For this, we implemented a series of heating steps with the brain tissue suspended in a buffer composed of 500 mM tris-HCl (pH 7.5) and 0.02% SDS after the standard deparaffinization of the tissue sections. Initially, samples from seven human brain samples, including four samples from patients diagnosed with dementia with Lewy bodies (DLB) and three samples from healthy controls without DLB, were compared to fresh frozen samples under three different, but clinically common sample storage conditions: formalin-fixed, FFPE, and FFPE slices cut 5 µm thick. The KASAR protocol was able to recover seeding activity for all positive samples in all storage conditions. Next, 28 FFPE samples from the submandibular gland (SMG) of patients diagnosed with PD, incidental Lewy body disease (ILBD), or healthy controls were tested with 93% of results replicating when blinded. Overall, our KASAR protocol unlocks and restores the seeding ability of formalin-fixed paraffin-embedded tissues for the amplification of biomarker protein aggregates in kinetic assays.